The definitive guide to the ARM Cortex-M0 - Yiu, Joseph (Newnes, 2011)
The ARM Cortex-M0 processor is a modern microcontroller architecture developed specifically for 8-bit and 16-bit applications. It is easy to program and brings significant advantages in terms of performance and energy efficiency. This is the first book written on the ARM Cortex-M0 processor, written for users of the rapidly growing family of ARM Cortex-M0 procerssor-based microcontrollers. It delivers detailed information on the processor architecture and is packed with examples on how to use it, and provides an overview of the software development flow, as well as information on how to locate problems in program code and software porting. The first and definitive book on the new ARM Cortex-M0 architecture targeting the large 8-bit and 16-bit microcontroller market Explains the Cortex-M0 architecture and how to program it using practical examples Written by an engineer at ARM who was heavily involved in its development.